The effects of cybercrime on student academic performance in Nigeria: A study of kwara state university Malete - Alfakoro, Abubakar S Yushau; Toyin ojo emmanuel (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2025)
Cybercrime is one of the most engaged form of crime usually perpetrated by student across Nigeria learning institutions today. Overtime, there has been decline in the level of student academic performance across tertiary institution. The objective of the paper is to examine the correlation between cybercrime and students’ academic performance in Nigeria using kwara State University, Malete as the study area. The study made use of both primary and secondary source of data gathering. The primary date consist of structured questioner, while the secondary data include journals, websites and textbooks. The primary data was latter analyzed using simple percentage and chi-square was used to test the hypothesis. The paper discovered that cybercrime has a significant negative effect on student academic performance in Kwara State University Malete. The study also discovered that cybercrime as also contributed to gangsterism, prostitution, indecency, among other bad social vices within the tertiary institutions. The study recommends that government should provide cybercrime education to enlighten student, it also recommend that adequate employment should be provided by government in other to reduce the rate of youth idleness and also provide limited access to internet for student apart for educational purposes among others recommendations.